Group B Streptococcus in surgical site and non-invasive bacterial infections worldwide: A systematic review and meta-analysis. (June 2019) - Collin, Simon M.; Shetty, Nandini; Guy, Rebecca; Nyaga, Victoria N.; Bull, Ann; Richards, Michael J.; van der Kooi, Tjallie I.I.; Koek, Mayke B.G.; De Almeida, Mary; Roberts, Sally A.; Lamagni, Theresa
Highlights: This review obtained data on group B Streptococcus infection from 67 countries. Group B Streptococcus is implicated in a small proportion of non-invasive infections. Group B Streptococcus causes 10% of caesarean section invasive surgical infections. Abstract: Objectives: The epidemiology of disease caused by group B Streptococcus (GBS; Streptococcus agalactiae ) outside pregnancy and the neonatal period is poorly characterized. The aim of this study was to quantify the role of GBS as a cause of surgical site and non-invasive infections at all ages. Methods: A systematic review (PROSPERO CRD42017068914) and meta-analysis of GBS as a proportion (%) of bacterial isolates from surgical site infection (SSI), skin/soft tissue infection (SSTI), urinary tract infection (UTI), and respiratory tract infection (RTI) was conducted. Results: Seventy-four studies and data sources were included, covering 67 countries. In orthopaedic surgery, GBS accounted for 0.37% (95% confidence interval (CI) 0.08–1.68%), 0.87% (95% CI 0.33–2.28%), and 1.46% (95% CI 0.49–4.29%) of superficial, deep, and organ/space SSI, respectively. GBS played a more significant role as a cause of post-caesarean section SSI, detected in 2.92% (95% CI 1.51–5.55%), 1.93% (95% CI 0.97–3.81%), and 9.69% (95% CI 6.72–13.8%) of superficial, deep, and organ/space SSI. Of the SSTI isolates, 1.89% (95% CI 1.16–3.05%) were GBS. The prevalence of GBS in community and hospital UTI isolates was 1.61% (1.13–2.30%) and 0.73% (0.43–1.23%), respectively. GBS was uncommonly associated with RTI, accounting for 0.35% (95% CI 0.19–0.63%) of community and 0.27% (95% CI 0.15–0.48%) of hospital RTI isolates. Conclusions: GBS is implicated in a small proportion of surgical site and non-invasive infections, but a substantial proportion of invasive SSI post-caesarean section.